Integration of dismantling operations into a value recovery plan for circular economy. (15th April 2017) - Cong, Liang; Zhao, Fu; Sutherland, John W.
Abstract: Traditional linear production mode "take-make-dispose" has brought about increasing resource scarcity, great environmental cost and endangered human health. To address the problem, the concept of circular economy has been introduced and accepted as a solution. In a circular economy, end-of-life (EOL) products can be introduced into multiple life cycles, which maximize the utility and value of components and materials. The economic viability of value recovery from an EOL product is greatly affected by the plan and technologies used for dismantling that product. This paper presents an approach to find a profitable EOL strategy, which includes a method for generating a dismantling transition matrix and making decisions on the best dismantling sequence, level, and EOL options for components/parts. A preservative disassembly transition matrix is a description of possible ways to disassemble a product into individual parts without any damage. A guideline is created to include destructive and automated operations in order to expand a preservative disassembly matrix into a dismantling transition matrix, because dismantling EOL products might produce more profit than pure preservative disassembly. Based on the dismantling transition matrix, binary integer programming is used to formulate EOL product value recovery while considering possible options for components/subassemblies as well as the transition cost between dismantling operations, tools costs, and recycling regulations or goals. A hard disk drive (HDD) is used as a case study to demonstrate the approach. Highlights: This paper considers automated/destructive operations in dismantling planning and creates a guideline. This paper also considers hazardous material removal and recycling target in value recovery. This paper proposes a comprehensive model for value recovery optimization. The paper investigates on the hard disk drive dismantling decision making.